2011
DOI: 10.1021/jp2003968
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure of Pure and N-Doped TiO2 Nanocrystals by Electrochemical Experiments and First Principles Calculations

Abstract: Optical and electrochemical characterizations are carried out in conjunction with first-principles calculations on pure and N-doped titania nanocrystals. These are prepared in laboratory with initial doping concentrations of triethylamine in the range of 0.1-0.5 N/Ti molar ratio. Diffuse reflectance UV-vis spectra of N-doped samples present a significant absorption in the visible region. The flatband potential (E fb ) of pure and nitrogen-doped TiO 2 (-0.6 ( 0.2 V vs NHE) is determined by impedance spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
99
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 93 publications
(69 reference statements)
8
99
0
2
Order By: Relevance
“…However there now appears to be some agreement regarding the fine electronic details of N doped visible light absorption as reported by Irie [8] and Nakamura [9]. It is now believed that oxygen lattice sites within the TiO 2 crystal are substituted by nitrogen atoms [10,11] form an occupied midgap (N 2p) level above the TiO 2 (O 2p) valence band. The N 2p band therefore acts as a step between the valence and the conduction band of the semiconductor, facilitating excitation of electrons from the N 2p mid-gap band to the conduction band upon irradiation with visible light [8,9].…”
Section: Introductionmentioning
confidence: 75%
“…However there now appears to be some agreement regarding the fine electronic details of N doped visible light absorption as reported by Irie [8] and Nakamura [9]. It is now believed that oxygen lattice sites within the TiO 2 crystal are substituted by nitrogen atoms [10,11] form an occupied midgap (N 2p) level above the TiO 2 (O 2p) valence band. The N 2p band therefore acts as a step between the valence and the conduction band of the semiconductor, facilitating excitation of electrons from the N 2p mid-gap band to the conduction band upon irradiation with visible light [8,9].…”
Section: Introductionmentioning
confidence: 75%
“…In contrast, at potentials more positive than E fb , the band bending creates a barrier (space charge layer) to electron transfer, and the sample shows a dielectric characteristic. Although a precise determination of the flat band potential is often complicated by the presence of surface states and defects unavoidably connected with the nanometer size of the passive film [75,76], the information on E fb provides useful guides to the understanding of electrochemical behavior. Many researchers have demonstrated that there was an intrinsic relationship between the localized corrosion resistance and the flat band potential of the passive film [77][78][79].…”
Section: Influence Of Nb Addition On the Electronic Properties Of Pasmentioning
confidence: 99%
“…30 For our samples, we measured open circuit voltages between -0.5 V and -0.7 V, which depended on the deposition pressure and annealing time/temperature. In general, the asdeposited films had slightly lower open circuit voltages, and as the annealing time increased, so did the open circuit voltage.…”
Section: Photoelectrochemical Performancementioning
confidence: 99%